Analiza efektywności technicznej w produkcji zwierzęcej w grupie gospodarstw towarowych Wielkopolski - Bieńkowski, Jerzy; Jankowiak, Janusz (Analysis of Technical Efficiency in Animal Production for the Group of Commercial Farms from Wielkopolska, 2006)
The aim of the research is to analyze technical efficiency in commercial farms with animal production. In the performed study, the nonparametric DEA method is applied. The data consiste of 2 farms' types - milk production (10 farms) and pig fattening (10 farms). The study was carried out during the period of 2002-2004. Efficiency of farms was compared by type of farming and also by size of farms. The mean overall efficiency was found to be around 0,83. It was shown that in dairy farms pure technical efficiency exceeded scale efficiency, while this relation was reversed in pig farms. The mean overall and pure technical efficiency decreased in acreage groups with larger agricultural land area and at the same time the scale efficiency increased.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 76-82